2003
DOI: 10.1046/j.1439-0469.2003.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome evolution in the genus Cicindela: physical mapping and activity of rDNA loci in the tiger beetle species Cicindela littoralis and C. flexuosa

Abstract: Cicindela littoralis and Cicindela flexuosa were analysed at population level to determine the localization and activity of ribosomal genes. Fluorescence in situ hybridization (FISH), using a PCR-amplified 18S rDNA fragment as a probe, revealed the presence of polymorphism regarding the number of chromosomes with ribosomal genes as well as their localization within the genome. Nine populations of C. littoralis showed a consistent pattern of two loci located in an autosomal pair (active during spermatogenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…The autosomal localization of these gene clusters as well as the higher number of copies resemble other data for basal groups, such as Amblycheila and Manticora (eight rDNA loci) and Omus and Megacephala (six rDNA loci) (Galián and Hudson, 1999;Galián et al, 2002). In M. sobrina and M. cruciata (with eight and five rDNA loci, respectively) the ribosomal clusters occupied a distal position as observed in other cicindelids (Galián et al, 1995;Galián and Hudson, 1999;Proença et al, 2002a;Proença and Galián, 2003). Also, the size of the fluorescent region varied in the different chromosomes, with one signal being much larger than the others, covering almost all the short arm of the chromosome in M. sobrina.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The autosomal localization of these gene clusters as well as the higher number of copies resemble other data for basal groups, such as Amblycheila and Manticora (eight rDNA loci) and Omus and Megacephala (six rDNA loci) (Galián and Hudson, 1999;Galián et al, 2002). In M. sobrina and M. cruciata (with eight and five rDNA loci, respectively) the ribosomal clusters occupied a distal position as observed in other cicindelids (Galián et al, 1995;Galián and Hudson, 1999;Proença et al, 2002a;Proença and Galián, 2003). Also, the size of the fluorescent region varied in the different chromosomes, with one signal being much larger than the others, covering almost all the short arm of the chromosome in M. sobrina.…”
Section: Discussionsupporting
confidence: 74%
“…Differences at population level regarding the number and distribution of ribosomal genes have already been described for the Cicindela species C. littoralis and C. flexuosa (Proença and Galián, 2003). In our study, however, an interesting aspect about the localization of ribosomal clusters was the presence of odd numbers of autosomal copies (three in M. rutilans and five in M. cruciata) since the same number of rDNA clusters should be expected in both homologous chromosomes.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…558 Proença et al In our research, the localization of major rDNA sites by FISH revealed different patterns for C. argentata, C. aurulenta and C. suturalis, with ribosomal clusters located in the autosomes, the heterosomes or in both. Different patterns regarding the localization of rDNA genes have been described in other Cicindela species : two clusters located in one autosomal pair (C. flexuosa, C. paludosa and C. hispanica); two clusters located in one autosomal pair and one in an X chromosome (C. littoralis and C. maura); two clusters located in one autosomal pair and two in the heterosomes (XY) (C. deserticoloides and C. circumdata) and three clusters located in the heterosomes (XXY) (C. trisignata) (see Proença et al, 2000;Proença and Galián, 2003). In our study we found two new rDNA localization patterns, i.e.…”
Section: Discussionmentioning
confidence: 99%